(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To summarize the effectiveness of hyperbaric oxygen therapy in the treatment of patients who underwent radiation therapy for head and neck cancer from 1992 to 2022. Subjects and methods: This systematic review uses the open data sources Pubmed, Google Scholar to search for articles and full-text researches written in English in accordance with the selection criteria. Results: The number of articles selected and included in the systematic review was 21. The results show that hyperbaric oxygen therapy is effective in reducing xerostomia, however, its effectiveness in reducing risk/accelerating healing process of osteoradionecrosis and improving patients’ quality of life has not been agreed. Conclusion: More well-designed randomized controlled trials with uniform protocols are needed to recommend the use of hyperbaric oxygen therapy for irradiated head and neck cancer patients.